Delayed diagnosis of congenital anorectal malformation - Daniel Ardian Soeselo; Garry Grimaldy; Susilawati (Elsevier, 2020)
Background: Congenital anorectal malformation is uncommon and often missed-diagnosed. The diagnosis can be late due to late presentation of the complaint. Physical examination of the neonates remains the first step towards diagnosing which has no standard practical guidelines even in multi-disciplined education center primary care. Case presentation: We present, a case of a late diagnosed low-level congenital anorectal malformation. Conclusion: Congenital anorectal malformation usually is easy to diagnose but often missed during physical examination at birth. Thus, making patient come with serious complications of the missed-diagnosed malformation.